Current Applications of Plant-Based Drug Delivery Nano Systems for Leishmaniasis Treatment - Santos, Darline B. dos; Lemos, Janaina A.; Miranda, Sued E. M.; Di Filippo, Leonardo D. [UNESP]; Duarte, Jonatas L. [UNESP]; Ferreira, Lucas A. M.; Barros, Andre L. B.; Oliveira, Anna E. M. F. M. (Mdpi, 2022)
Leishmania is a trypanosomatid that causes leishmaniasis. It is transmitted to vertebrate hosts during the blood meal of phlebotomine sandflies. The clinical manifestations of the disease are associated with several factors, such as the Leishmania species, virulence and pathogenicity, the host-parasite relationship, and the host's immune system. Although its causative agents have been known and studied for decades, there have been few advances in the chemotherapy of leishmaniasis. The urgency of more selective and less toxic alternatives for the treatment of leishmaniasis leads to research focused on the study of new pharmaceuticals, improvement of existing drugs, and new routes of drug administration. Natural resources of plant origin are promising sources of bioactive substances, and the use of ethnopharmacology and folk medicine leads to interest in studying new medications from phytocomplexes. However, the intrinsic low water solubility of plant derivatives is an obstacle to developing a therapeutic product. Nanotechnology could help overcome these obstacles by improving the availability of common substances in water. To contribute to this scenario, this article provides a review of nanocarriers developed for delivering plant-extracted compounds to treat clinical forms of leishmaniasis and critically analyzing them and pointing out the future perspectives for their application.
Keywords: Leishmania control; neglected diseases; natural products; nanosystems